Particulate Matter and Labor Supply : The Role of Caregiving and Non-Linearities - Aragon, Fernando M.; Miranda, Juan Jose; Oliva, Paulina (World Bank, Washington, DC, 2016)
This paper examines the effect of air pollution on labor supply in Lima, Peru. It focuses on fine particulate matter (PM2.5), an important pollutant for health according to the medical literature, and shows that moderate levels of pollution reduce hours worked for working adults. The research design takes advantage of rich household panel data in labor outcomes to address omitted variables and allows investigation of whether the response to air pollution is non-linear. The analysis finds that the effect of moderate pollution levels on hours worked is concentrated among households with susceptible dependents, that is small children and elderly adults, while the highest concentrations affect all households. This suggests that caregiving is likely a mechanism linking air pollution to labor supply at moderate levels. Further evidence of this mechanism is provided using DHS data on children morbidity for the same time period. Finally, no evidence is found of intra-household attenuation behavior. For instance, there is no re-allocation of labor across household members, and earnings decrease with air pollution.